PERBANDINGAN HASIL PEMERIKSAAN KADAR ASAM URAT MENGGUNAKAN METODE POCT (Point of Care) DENGAN METODE SPEKTROFOTOMETRI PADA LANSIA - Maudiva Hafsyah Maryani; Nurul Hanifah Fadhillah; Ela Melani MS (LPSDI Bina Patria, 2022)
Examination of uric acid can be tested through the spectrophotometric method and the point of care testing (POCT) method. Given that Spectrophotometry has high sensitivity and specificity, while POCT has poor accuracy. POCT is usually used if there is an urgent situation such as damage to the Spectrophotometry tool. In this study, the POCT tool with the Autocheck brand was used. . The purpose of study: To compare the results of uric acid using a POCT device that uses capillary blood with spectrophotometry that uses serum in the elderly. Methods: Examination using an autocheck tool with the principle of POCT (Point of care Testing) where when blood is dripped on a strip, the uric acid catalyst triggers the oxidation of uric acid in the blood and Spectrophotometry with the principle of absorption of light at a certain wavelength region. Sampling was carried out on men and women starting at the age of 50 years. Results: The results of uric acid levels using strips (POCT) ranged from 3.9-9.2 mg/dl with a median value of 6.15 mg/dl and the results on a spectrophotometer ranged between 3.44-8.91 with a mean value of 5.12 mg/dl. Conclusion : The differences in the measurements POCT and spectrophotometry can be caused by several factors